Chest wall and rib irradiation and toxicities of early-stage lung cancer patients treated with CyberKnife stereotactic body radiotherapy. (December 2014) - Podder, Tarun; Biswas, Tithi; Yao, Min; Zhang, Yuxia; Kim, Ellen; Ellis, Rodney J; Lo, Simon S; Machtay, Mitchell
ABSTRACT : Aim: The aim of the study is to evaluate the chest wall and rib toxicities in primary lung cancer patients treated with CyberKnife-based stereotactic body radiotherapy.Materials & methods: In this study, data were collected from the 118 patients, of which 25 patients who had longer follow-up (mean: 21.9 months) were considered. Studied parameters were maximum point dose, doses to 1–100 cm 3 of chest wall and 1–10 cm 3 of ribs.Results: Three patients developed chest wall pain (grade I). 25 studied patients, on average, received 27.7 Gy to 30 cm 3 of chest wall and 50.4 Gy to 1 cm 3 of rib. Nine patients had more than 30 Gy dose to 30 cm 3 of chest wall. No rib bone fracture was found.Conclusion: No correlations of chest wall pain and volume of irradiation were found.